Pituitary dysfunction from an unruptured ophthalmic internal carotid artery aneurysm with improved 2-year follow-up results: A case report - Qi Meng; Ye Ming; Li Meng; Zhang Peng (Open Medicine, 2018)
Internal carotid artery (ICA) supraclinoid segment aneurysms extending into the sellar region and leading to pituitary dysfunction are a rare occurrence. To date, long-term follow up of pituitary function 2 years post-treatment has never been reported. Herein, we present a case of pituitary dysfunction due to an unruptured ophthalmic segment internal carotid artery aneurysm and report improved 2-year follow-up results. A 76-year-old male presented with disturbed consciousness due to hyponatremia, which was caused by hypoadrenocorticism resulting from pituitary dysfunction complicated by hypogonadism and hypothyroidism. Computed tomography angiography revealed an intracranial aneurysm of the ophthalmic segment of the right ICA with an intrasellar extension. Thus, digital subtraction angiography and coil embolization were performed, followed by hormone replacement therapy. A 2-year follow-up revealed a partial improvement in the pituitary function, including complete restoration of thyroid-stimulating hormone level and other thyroid hormones levels, and partial restoration of testosterone levels, followed by discontinuation of thyroid hormone replacement therapy. However, the mechanisms of such pituitary dysfunction and the effects of various treatments, including clipping and coiling, on different hormones of pituitary function recovery remain unclear. A long-term follow-up of >2 years may elucidate the pituitary function recovery post-treatment and provide a medication adjustment for hormone replacement therapy.